Callous–Unemotional Traits and Response to Functional Family Therapy in Adolescent Offenders. (21st November 2012) - White, Stuart F.; Frick, Paul J.; Lawing, Kathryn; Bauer, Daliah
<x xml:space="preserve">Abstract</x> OBJECTIVE The current study examined whether callous–unemotional (CU) traits moderated the effectiveness of Functional Family Therapy for juvenile justice involved adolescents. METHOD Participants were all youths (n = 134) who had been arrested and participated in an FFT program provided in a community mental health center over a 20‐month period (mean age 15.34, 71.6% males, 59% African‐American). Parent and self‐report ratings of emotional, behavioral, and social functioning, multi‐informant ratings of treatment progress, and probation/arrest records were used as outcome indicators. RESULTS CU traits were associated with poorer behavioral, emotional, and social adjustment prior to treatment but they were also associated with greater improvements in adjustment over the course of treatment. CU traits were not associated with significantly lower rates of participation or higher rates of treatment dropout, and the association between CU traits and risk for violent charges decreased after treatment at 6‐ and 12‐month follow‐ups. However, CU traits were still correlated with poorer levels of adjustment post‐treatment, less perceived change over treatment by youth and their parents, and increased likelihood of violent offending during treatment. CONCLUSIONS The results of this study indicate that FFT can lead to improvements in youth with CU traits; however, they enter treatment with a greater number of symptoms and are at higher risk for committing violence during treatment than other youth. Copyright © 2012 John Wiley & Sons, Ltd.